2018
DOI: 10.1080/21691401.2018.1505740
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin–albumin cluster: physiological responses after exchange transfusion into rats and blood circulation persistence in dogs

Abstract: A core-shell protein cluster comprising hemoglobin and human serum albumins, hemoglobin-albumin cluster (Hb-HSA 3), was designed and synthesized for use as an artificial O 2 carrier and red blood cell (RBC) substitute. For initial preclinical safety evaluation of the Hb-HSA 3 solution, we observed blood compatibility in vitro, physiological responses after exchange transfusion into rats and blood circulation lifetime in dogs. Dilution of human whole blood with Hb-HSA 3 showed an appropriate decrease in blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Preclinical studies into the safety of PNPs decorated with Pt clusters found longer half‐lives, no negative effects on vital organs, and serum biochemical markers that indicated no abnormalities when compared to the control group. [ 331 , 332 , 333 ]…”
Section: Protein Particles In Nanomedicinementioning
confidence: 99%
“…Preclinical studies into the safety of PNPs decorated with Pt clusters found longer half‐lives, no negative effects on vital organs, and serum biochemical markers that indicated no abnormalities when compared to the control group. [ 331 , 332 , 333 ]…”
Section: Protein Particles In Nanomedicinementioning
confidence: 99%
“…We earlier demonstrated a triangular protein cluster consisting of a Hb in the center and human serum albumins (HSAs) at the periphery (Hb‐HSA 3 ) as an artificial O 2 ‐carrier (red blood cell substitute) [14–17] . The safety and efficacy of Hb‐HSA 3 have been evaluated using animal experiments [18,19] . It is remarkable that the outside HSA moieties of Hb‐HSA 3 incorporate various hydrophobic molecules.…”
Section: Figurementioning
confidence: 99%
“…We earlier reported the synthesis and O 2 ‐binding property of core‐shell protein cluster consisting of a bovine hemoglobin (Hb) and human serum albumins (HSA), Hb‐HSA 3 cluster (Figure 1A). Safety and efficacy of this artificial O 2 ‐carrier solution ([Hb unit] = 5 g/dL, Figure 1B) as a red blood cell (RBC) substitute have been proven by animal experiments . However, the oxygenated Hb (oxyHb) core in the cluster is gradually oxidized to ferric metHb even at 4°C, and eventually loses the O 2 ‐transporting ability.…”
Section: Introductionmentioning
confidence: 97%